2016
DOI: 10.1101/062570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Manipulating virulence factor availability can have complex consequences for infections

Abstract: Given the rise of bacterial resistance against antibiotics, we urgently need alternative strategies to fight infections. Some propose we should disarm rather than kill bacteria, through targeted disruption of their virulence factors. It is assumed that this approach (i) induces weak selection for resistance because it should only minimally impact bacterial fitness, and (ii) is specific, only interfering with the virulence factor in question.Given that pathogenicity emerges from complex interactions between pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…We then used Galleria mellonella larvae as a model to reproduce the spatial structure P. aeruginosa would face in a host during an infection [27]. We infected larvae with mono-and mixed cultures in the presence or absence of gentamicin following a standard protocol of infection [28], using 10 2 -10 3 cells as the inoculum. Single strain infections were performed with MPAO1, ∆fpvA and ∆fpvB in order to obtain survival curves of the animal host in the presence and absence of gentamicin.…”
Section: The ∆Fpvb Mutant Is a Suitable Trojan Horse In Structured Biofilms And In An Animal Modelmentioning
confidence: 99%
“…We then used Galleria mellonella larvae as a model to reproduce the spatial structure P. aeruginosa would face in a host during an infection [27]. We infected larvae with mono-and mixed cultures in the presence or absence of gentamicin following a standard protocol of infection [28], using 10 2 -10 3 cells as the inoculum. Single strain infections were performed with MPAO1, ∆fpvA and ∆fpvB in order to obtain survival curves of the animal host in the presence and absence of gentamicin.…”
Section: The ∆Fpvb Mutant Is a Suitable Trojan Horse In Structured Biofilms And In An Animal Modelmentioning
confidence: 99%
“…As expected, we observed that all the siderophore genes were significantly upregulated under iron limitation. The expression of toxA and prpL (piv), encoding exotoxinA and protease IV, which are known to be induced in the presence of pyoverdine [44,45], were also significantly upregulated under iron limitation. Next, we focused on two genes encoding the superoxide dismutase SodB (iron-dependent) and SodM (manganese-dependent).…”
Section: Expression Of Siderophore Genes and Other Iron-regulated Gen...mentioning
confidence: 99%
“…It evolves because antibiotics kill bacteria, and the widespread use of these drugs thus imposes strong selection on the bacteria to survive in their presence. On this basis, a view has emerged that a more evolutionarily robust approach would be to target virulence factors—the microbial molecules responsible for pathogenesis—in order to “disarm rather than kill” the pathogen (Weigert et al, 2017), and there is a growing literature on different aspects of this approach as well as the potential consequences of its implementation (Allen et al, 2014; Brown, Cornforth, & Mideo, 2012; Cegelski, Marshall, Eldridge, & Hultgren, 2008; Defoirdt, 2016; Vale et al, 2016; Wollein Waldetoft & Brown, 2017).…”
Section: Research At the Crossroadsmentioning
confidence: 99%